The transformations and legacies of the neapolitan pedagogical model: a small reflection based on João Sépe’s treatise - Tavares, Fernando (2024)
This article explores the evolution of the Neapolitan pedagogical model, focusing on the works of Fedele Fenaroli (versions from 1775 and 1847) and João Sépe (released in 1942). It highlights how the book “Regole musicali per i principianti di cembalo”, released by Fenaroli, witnessed changes in musical thought throughout the 19th century and had similarities with the exercises of harmony and counterpoint, in João Sépe's “Treaty of Harmony”, widely used in music schools in Brazil. To this end, firstly, we compared the format of writing the exercises and discussed the teaching model through instructional basses. Afterwards, we present a comparative model of the four fundamental musical teachings of the partimento notebooks: Rule of the Octave, Cadences, Suspensions and Bass Movements. Furthermore, we present a brief discussion about the forms of modulations that we found in the authors. Finally, we demonstrate how the harmonic realization, transmitted through the basses, gains prominence, highlighting the strength of the chord as a harmonic unit in relation to the contrapuntal passages.